2017
DOI: 10.1177/1069072717714537
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Supports and Barriers and Career and Educational Outcomes

Abstract: Interest in the roles of environmental supports and barriers in career and educational development has increased steadily over the past few decades, enough to warrant a meta-analysis of this vast and still growing literature. The current study presents the results of a meta-analytic investigation, employing 276 samples drawn from 249 published articles ( N = 104,440), on the relationships of supports and barriers to nine different career and educational outcomes. Employing a random effects meta-analytic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Future research may also benefit from incorporating work conditions and outcomes into studies of academic satisfaction. This suggestion is consistent with findings linking campus climate and discrimination to college satisfaction, performance, and retention (Brown et al, 2018). We also think that outcome expectations deserve more study in research on work satisfaction.…”
Section: Directions For Future Research and Practicesupporting
confidence: 92%
“…Future research may also benefit from incorporating work conditions and outcomes into studies of academic satisfaction. This suggestion is consistent with findings linking campus climate and discrimination to college satisfaction, performance, and retention (Brown et al, 2018). We also think that outcome expectations deserve more study in research on work satisfaction.…”
Section: Directions For Future Research and Practicesupporting
confidence: 92%
“…As stigma consciousness was a negative predictor of self-efficacy, it may be inferred to carry the deleterious effects of low self-efficacy on persistence and goal behaviors (Brown et al, 2008;Lee et al, 2015;Robbins et al, 2004;Wright, Jenkins-Guarnieri, & Murdock, 2012). This result also confirms Brown et al's (2018) meta-analysis in regard to relationships among supports and barriers and career and educational outcomes where they documented discrimination as a barrier accounted for approximately 9% of the variance in academic persistence, versus 1% or less of the variance for the other career and educational outcomes. This suggests the importance of continued efforts to reduce discrimination and promote equality in the school environment.…”
Section: Chapter V Discussionsupporting
confidence: 83%
“…Additionally, coping efficacy for barriers to education and career was included as a variable that could lead to an understanding of how levels of confidence in responding to educational/career barriers might buffer the effect of negative racial/ethnic stigma consciousness. Thus, this study extends SCCT by incorporating a new construct and also including negative outcome expectations in the model, responding to a call for advancing research on SCCT with implications for potential interventions to help individuals in coping with environmentally imposed barriers (Brown et al, 2018;Lent et al, 2000).…”
Section: Chapter V Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meaningful way to measure perceived barriers in populations that embrace the themes found in our qualitative analysis—bootstrapper mentality, practical disconnect, localism, positive future mind-set, and lack of urgency—is vital in being able to design and deliver effective and meaningful career education and counseling interventions. Brown et al (2018) noted that researchers agree barriers negatively impact career and academic beliefs, but questions still exist about the magnitude and direction of these effects on SCCT variables. In the results of their meta-analysis of quantitative studies, they found that barriers only had a small effect on other SCCT outcome variables and suggested that focusing on support building may be more effective than barrier reduction.…”
Section: Overall Implications and Limitationsmentioning
confidence: 99%